DIFFERENCES IN PULSE RATE AND LACTIC ACID LEVELS IN ATHLETES BEFORE AND AFTER LIGHT AND MEDIUM INTENSITY PHYSICAL ACTIVITIES - Aditya Candra; Tahara Dilla Santi; Muhammad Yani; Said Aandy Saida; Ika Waraztuty; Andri; Fuadi; Farid Bastian; Zurriyani (PT. Radja Intercontinental Publishing, 2024)
Strenuous exercise can trigger an increase in pulse rate and lactic acid levels. Stress during exercise can secrete adrenaline so that your heart rate increases, and free radicals including lactic acid. This study aims to determine the effect of light and moderate-intensity aerobic exercise on lactic acid levels and pulse rate during exercise. The research carried out was a quasi-experimental research with a non-random repeat experiment design. Pulse rate and lactic acid levels were assessed before and after the exercise program in 3 groups, namely the light-intensity aerobic exercise (LAIR) treatment group, the moderate-intensity aerobic exercise (LAIS) group, and the control group. The research location is the Harapan Bangsa football stadium in Banda Aceh. The subject is Aceh Diaspora PPLP athlete. The training program was carried out for four weeks. The mean pulse rate and lactic acid levels of the three groups showed differences. A significant decrease in heart rate values ​​after the training test was seen in the group with LAIS (p = 0.000). A significant decrease in lactic acid after the training test was seen in the group with LAIS (p= 0.04). The mean pulse rate of the three groups showed differences. An exercise program carried out with the right intensity, duration, and frequency can reduce increases in heart rate and lactic acid levels. This research shows that moderate-intensity aerobic exercise can reduce pulse rate and lactic acid levels so that it can slow down fatigue during exercise in Acehnese football athletes.